Assessing Medical Students’ Interest in Community Medicine/Public Health as a Career Path: A Cross-Sectional Study at Sahiwal Medical College, Sahiwal, Pakistan: Medical Students’ Interest in Community Medicine/Public Health as A Career Path - Menahal, .; Hussain, Mushayyad; Rehm, Muhammad Hassam; Hassaan, Muhammad; Iftikhar, Hira; Haq, Muhammad Imran Ul (Pakistan Journal of Health Sciences, 2025)
Public health should be the priority of underdeveloped countries like Pakistan to have better management plans for combating diseases. But it was observed that medical students are less interested in a career as a public health specialist, and they are less inclined towards community medicine. Objectives: To determine the preferences of the undergraduate medical students towards the choice of subject for specialization and to determine their attitude towards community medicine as a future career. Methods: A cross-sectional questionnaire-based study was conducted at a public sector medical college of Punjab using a convenient sampling technique. After receiving approval and having informed consent from the 315 study participants, we shared the questionnaire via WhatsApp in the form of Google Forms. The data were then analyzed using SPSS version 26.0. Results: Out of the total 315 participants, 170(54%) were females and 145 (46%) were males. The majority (96%) of the students were inclined towards opting for clinical sciences after graduation. Surgery 139 (44.1%) and Medicine 84 (26.6%) were the most preferred fields for specialization, only 9(2.8%) students preferred community medicine (p-value=0.001). When asked for the reason for not choosing community medicine, the majority, 189 (60%), said that they are not impressed by this subject. Career dissatisfaction was identified as the second main reason (14.6%) for not opting for this subject as a future career path. Conclusions: It was concluded that appropriate teaching methodology should be adopted and the curriculum should be designed in such a way that it may increase students’ interest in community medicine.